2020
DOI: 10.3390/app10165553
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Electron and Hole Transfer Dynamics from CH(NH2)2PbI3 Perovskite Quantum Dots to Charge Transport Layers

Abstract: In this work, the ultrafast transient absorption spectroscopy (TAs) was utilized to first investigate the charge transfer from the emerging FAPbI3 (FA = CH(NH2)2) perovskite quantum dots (PQDs) to charge transport layers. Specifically, we compared the TAs in pure FAPbI3 PQDs, PQDs grown with both electron and hole transfer layers (ETL and HTL), and PQDs with only ETL or HTL. The TA signals induced by photoexcited electrons decay much faster in PQDs samples with the ETL (~20 ps) compared to the pure FAPbI3 PQDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To further explore the carrier dynamics of the photoactive layer with NCs and HTLs, transient absorption spectroscopy (TA) measurement [27][28][29][30] was performed, as shown in Fig. 6b.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the carrier dynamics of the photoactive layer with NCs and HTLs, transient absorption spectroscopy (TA) measurement [27][28][29][30] was performed, as shown in Fig. 6b.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the charge transfer ability in FAPbI 3 QDSCs depended on the interfacial interaction between the PQD/charge transport layer heterojunctions. [43,44] To achieve efficient charge separation and transfer in FAPbI 3 QDSCs, introducing small or polymer molecule with conjugated structure in PQDs could enhance charge carrier extraction and reduce recombination at PQD/charge transport layer interfaces. [45,46] As a result, the PCE of FAPbI 3 PQDs-based devices could achieve 13%.…”
Section: The Optimization Of the α-Fapbi 3 Pscs Preparationmentioning
confidence: 99%
“…These layers facilitate the extraction of charge carriers and minimize the internal recombination. The ultrafast charge transfer (CT) relies on the electronic coupling and interfacial interaction between PQDs and charge-transporting layers . The efficiency of hole transfer from pure PQDs to the HTL may not be satisfactory, in particular for the HTL PTAA, , which has higher hole mobility and is cheaper than Spiro-OMeTAD and considered as the ideal choice for the practical device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast charge transfer (CT) relies on the electronic coupling and interfacial interaction between PQDs and charge-transporting layers . The efficiency of hole transfer from pure PQDs to the HTL may not be satisfactory, in particular for the HTL PTAA, , which has higher hole mobility and is cheaper than Spiro-OMeTAD and considered as the ideal choice for the practical device applications. The ineffective hole extraction due to the large surface energy difference between PQDs and an organic HTL is one of the main reasons limiting the power conversion efficiency (PCE) of perovskite-based devices. , A heterointerface consisting of a conjugated polymer and PQDs is an alternative strategy to provide an additional channel to facilitate the CT .…”
Section: Introductionmentioning
confidence: 99%